Predictive performance of the Mayo Clinic and New York Risk Scores in percutaneous coronary intervention: A single-center study from Vietnam - Tu, Hoang Minh Thanh; Tien, Hoang Anh; Yen, Hoang Thi Bach; Thang, Doan Chi; Long, Huynh Thai (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Risk stratification is essential in patients undergoing percutaneous coronary intervention (PCI), particularly for predicting early complications and in-hospital mortality. This study evaluated the Mayo Clinic Risk Score (MCRS) and the New York Risk Score (NYRS) in patients undergoing PCI at Vietnam-Cuba Friendship Hospital, Dong Hoi. Methods: This was a single-center cross-sectional descriptive study with follow-up from PCI initiation to hospital discharge. A total of 102 hospitalized patients undergoing PCI between June 2024 and January 2025 were included. Patients were classified into emergency PCI (n = 60) and elective PCI (n = 42) groups. Baseline clinical, laboratory, echocardiographic, angiographic, and procedural data were collected. Complication risk was assessed using MCRS, and mortality risk using NYRS. Predictive performance was evaluated using receiver operating characteristic (ROC) analysis. Logistic regression was performed to identify independent predictors of in-hospital complications and mortality. Results: The mean age was 70.1 ± 11.8 years, and 72.6% were male. Emergency PCI patients had significantly higher median MCRS and NYRS than elective PCI patients (11 vs. 5 and 10 vs. 5, respectively; both p < 0.001). Overall, 18.6% of patients developed in-hospital complications and 2.9% died. Reperfusion syndrome was more frequent in emergency PCI (13.3% vs. 0%, p = 0.020), whereas periprocedural myocardial infarction was observed only in elective PCI patients (11.9% vs. 0%, p = 0.010). For predicting in-hospital complications, MCRS showed modest discrimination (AUC 0.640, p = 0.041; cut-off >9). For predicting in-hospital mortality, NYRS showed excellent discrimination (AUC 0.907, p < 0.001; cut-off >11). In multivariable analysis, NYHA class III-IV independently predicted complications (OR 4.191, p = 0.016), while cardiogenic shock independently predicted in-hospital mortality (OR 7.373, p = 0.028). Conclusion: Emergency PCI patients had a higher risk profile and worse short-term outcomes than elective PCI patients. Both MCRS and NYRS were clinically useful for early risk stratification, with MCRS showing modest value for predicting complications and NYRS demonstrating excellent performance for predicting in-hospital mortality.